global crisis and noospheric paradigm of sustainable development (Eurasian Journal of Ecology, 2016)
Consider the system of multi-dimensional projection of the modern trends of the global crisis, the state and the causes. it is shown that all of these fundamentally new phenomena and processes require a deep scientific understanding, identifying their main objective and trends, develop scenarios and forecasts of the global strategy for sustainable development. it is concluded that the yield of a systemic crisis is possible only on the basis of a synthesis of scientific knowledge about the laws of "nature - society - people," and "sustainable development" is directly related to the growth of the free energy on the planet and is the fundamental basis for sustainable innovative development.
Keywords: sustainable development; global crisis; “nature – society – man” system; noospheric ltlanguage; design and management; transition to noosphere.